First genetic characterization of Peste des Petits Ruminants from Niger: On the advancing front of the Asian virus lineage - Tounkara, Kadidia; Bataille, Arnaud; Adombi, Caroline M.; Maikano, Issoufou; Djibo, Gamatié; Settypalli, Tirumala Bharani K.; Loitsch, Angelika; Diallo, Adama; Libeau, Geneviève (Transboundary and emerging diseases, 2018)
Summary Peste des Petits Ruminants (PPR) is a serious transboundary infectious disease of small ruminants. The causal agent, PPR virus (PPRV), can be separated into four genetically distinct lineages using phylogenetic analysis. In recent decades, lineage IV of PPRV has dramatically extended its geographic distribution from Asia to the Middle East and to Africa, where it has progressively replaced other PPRV lineages. Lineages I and II are historically distributed in West Africa. Currently, lineage II appears to dominate the region, whereas the last recorded occurrence of lineage I dates back to 1994. Recent studies reported the presence of lineage IV in Nigeria, suggesting that this lineage is expanding in West Africa. In Niger, a close neighbour of Nigeria, PPRV has never been genetically characterized, despite reports of PPR incidence. In this study, pathological samples collected from sick goats were collected in 2013 during a suspected PPR outbreak in southern Niger close to the Nigerian border were compared to samples collected in a previous investigation in October 2001 in south‐western Niger. These strains were characterized by sequencing and phylogenetic analysis to identify their genetic lineage. Our results show that in 2001, lineages I and II were cocirculating in south‐western Niger, whereas the strain that caused the outbreak in 2013 belonged to lineage IV and is closely related to strains identified in Nigeria. These results confirm the progression of lineage IV in West Africa. The process of PPRV lineage replacement and its implications for the epidemiology and the control of the disease in this region are unclear and should be the subject of further studies in the field.